A representação da vilã em Once Upon a Time: uma análise de estereótipos de bem e mal a partir da abordagem multimodal e da semiótica social - Jacyara Sheyla dos Santos Martins Xavier (2019)
This thesis presents an analysis of the character Evil Queen represented by Regina Mills in the series Once Upon a Time, premiered in 2012 in Brazil. The analysis focuses on the first three seasons of the series and seeks to investigate the representations of stereotypes of good and evil based on the Multimodal Approach (JEWITT, BEZEMER, O'HALLORAN, 2016, KRESS, VAN LEEUWEN, 2001) and Social Semiotics (HODGE; KRESS, 1988; VAN LEEUWEN, 2005). Additionally, this research is underpinned by studies of Foucault (1975, 1999) and Nietzsche (1887; 2009) specially by their concepts of power, good and evil. Our methodological procedures bring together contributions from Multimodal Theory of the Moving Image including Burn (2013) and Pimenta (2006) as well. Through such perspectives, we emphasize the interplay between semiotic modes involved in the representation of the villain. To achieve such purpose, we compare some examples of visual stereotypes in the classic animation of Snow White from Disney, premiered in Brazil in 1938. The results indicate that certain strategies used by the producers have attempted to persuade the spectator to engage with the character, that is, their representations oscillated between good and evil, which underlie a more realistic instead of delusional identity as representations of fictional characters.